2021
DOI: 10.1186/s13012-021-01173-5
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of de-implementation frameworks and models

Abstract: Background Reduction or elimination of inappropriate, ineffective, or potentially harmful healthcare services and public health programs can help to ensure limited resources are used effectively. Frameworks and models (FM) are valuable tools in conceptualizing and guiding the study of de-implementation. This scoping review sought to identify and characterize FM that can be used to study de-implementation as a phenomenon and identify gaps in the literature to inform future model development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 85 publications
0
41
0
2
Order By: Relevance
“…For example, Helfrich et al highlighted that de-implementation may require a process of unlearning to change knowledge, intentions, and beliefs about a low-value service [ 46 ]. Recent reviews identified some theories, models, or frameworks specifically developed for the de-implementation of low-value care [ 59 , 60 ]. Using theoretical frameworks specifically developed for de-implementation of low-value care therefore may help researchers to better evaluate the de-implementation process, identify determinants of de-implementing low-valued care, and explore interactions among de-implementation determinants (e.g., peer pressure may moderate the influence of guidelines) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Helfrich et al highlighted that de-implementation may require a process of unlearning to change knowledge, intentions, and beliefs about a low-value service [ 46 ]. Recent reviews identified some theories, models, or frameworks specifically developed for the de-implementation of low-value care [ 59 , 60 ]. Using theoretical frameworks specifically developed for de-implementation of low-value care therefore may help researchers to better evaluate the de-implementation process, identify determinants of de-implementing low-valued care, and explore interactions among de-implementation determinants (e.g., peer pressure may moderate the influence of guidelines) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although disinvestment is frequently associated with budgetary concerns and affordability, it can also be prompted to enhance efficiency and quality of care through reformation of service provision (26). Based on our analysis (see Supplementary Tables 5 and 6), the purpose of disinvestment initiatives can be grouped into four themes (Figure 3): (i) enhance value-based spending (13;14;1619;25); (ii) resource reallocation (3;12;1421;24;25); (iii) improving quality of health care (3;7;1114;16;19;21;22;25); and (iv) informed policy making (12;17). Clarifying the goals of disinvestment would help people understand that it is a tool for improving access to effective solutions, not for eliminating technologies and withdrawing resources on a large scale.
Figure 3.Rationale and purpose of disinvestment.
…”
Section: Resultsmentioning
confidence: 99%
“…This data must be used in combination with state, national, and global data on case counts; the best available scientific evidence for understanding disease spread mechanisms and the effectiveness, and failure, of disease mitigation procedures to support dynamic decision‐making about implementation and de‐implementation strategies as local conditions change. 22 One example of community use of local data to identify vulnerable populations to target community outreach is the non‐profit Parkland Center for Clinical Innovation (PCCI) in Dallas, Texas. PCCI has led the creation of the Dallas Connected Community of Care (CCC) that brings together health systems, social service agencies and over a hundred community organizations to improve the well‐being of Dallas residents.…”
Section: Discussionmentioning
confidence: 99%